2011
DOI: 10.1371/journal.pone.0017435
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin, Sleep Reduction and Evening Preference: Relationships to CLOCK 3111 T/C SNP and Weight Loss

Abstract: Background Circadian Locomotor Output Cycles Kaput (CLOCK), an essential element of the positive regulatory arm in the human biological clock, is involved in metabolic regulation. The aim was to investigate the behavioral (sleep duration, eating patterns and chronobiological characteristics) and hormonal (plasma ghrelin and leptin concentrations) factors which could explain the previously reported association between the CLOCK 3111T/C SNP and weight loss.Methodology/Principal FindingsWe recruited 1495 overweig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
99
1
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(112 citation statements)
references
References 35 publications
9
99
1
2
Order By: Relevance
“…Of note, these new data related to DNA methylation are consistent with previous results related to CLOCK genetic variants, which demonstrated that sleep reduction, changes in ghrelin values, alterations of eating behaviors and evening preference are all connecting genetics, chronodisruption and obesity. 34 These results support the hypothesis that the influence of the clock genes may be extended to a broad range of variables linked with human behavior and metabolism. Moreover, our data pave the way to the study of epigenetic mechanisms in the regulation of circadian rhythms in relation to obesity and weight loss.…”
Section: Epigenetics Chronobiology and Obesitysupporting
confidence: 77%
See 2 more Smart Citations
“…Of note, these new data related to DNA methylation are consistent with previous results related to CLOCK genetic variants, which demonstrated that sleep reduction, changes in ghrelin values, alterations of eating behaviors and evening preference are all connecting genetics, chronodisruption and obesity. 34 These results support the hypothesis that the influence of the clock genes may be extended to a broad range of variables linked with human behavior and metabolism. Moreover, our data pave the way to the study of epigenetic mechanisms in the regulation of circadian rhythms in relation to obesity and weight loss.…”
Section: Epigenetics Chronobiology and Obesitysupporting
confidence: 77%
“…[32][33][34][35][36][37][38][39][40][41] Indeed, obesity is a heterogeneous condition and individual responses to standardized protocols targeting weight loss are highly variable. 2 In real life settings such as obesity treatment programs, physiological and psychological factors, some of which may carry a strong ge netic influence, interact with environmental factors in a complex manner.…”
Section: Time Of Foodmentioning
confidence: 99%
See 1 more Smart Citation
“…Clock and Bmal1 gene polymorphisms in humans suggest that genetic variation in these genes may play a role in the development of obesity and type 2 diabetes (Scott et al, 2008;Sookoian et al, 2008;Woon et al, 2007). Single-nucleotide polymorphisms (SNPs) in CLOCK are correlated with elevated plasma ghrelin levels, reduced sleep duration and increased energy intake (Garaulet et al, 2010(Garaulet et al, , 2011. Furthermore, carriers of CLOCK SNPs display lower plasma glucose concentrations and improved insulin sensitivity when they eat a diet rich in mono-unsaturated fatty acids Garcia-Rios et al, 2014).…”
Section: Deleterious Effects Of Circadian Desynchronization On Metabomentioning
confidence: 99%
“…Garaulet et al 40 reported associations between CLOCK3111T/C allele genotype and ghrelin but not leptin levels. Individuals who were carriers of the C allele had higher ghrelin levels than those with TT genotype.…”
Section: 36mentioning
confidence: 99%